Offshore system safety and operational challenges in harsh Arctic operations - Sidum Adumene; Hope Ikue-John (Journal of Safety Science and Resilience, 2022)
Offshore oil and gas drilling operations are going to remote and harsh arctic environments with demands for heightened safety and resilience of operational facilities. The remote and harsh environment is characterized by extreme waves, wind, storms, currents, ice, and fog that hinder drilling operations and cause structural failures of critical offshore infrastructures. The risk, safety, reliability, and integrity challenges in harsh environment operations are critically high, and a comprehensive understanding of these factors will aid operations and protect the investment. The dynamics, environmental constraints, and the associated risk of the critical offshore infrastructures for safe design, installation, and operations are reviewed to identify the current state of knowledge. This paper introduces a systematic review of harsh environment characterization by exploring the metocean phenomena prevalent in harsh environments and their effects on the floating offshore structures performance and supporting systems. The dynamics of the floating systems are described by their six degrees of freedom and their associated risk scenarios. The systematic methodology further explores the qualitative, quantitative, and consequences modeling techniques for risk analysis of floating offshore systems in a harsh environment. While presenting the current state of knowledge, the study also emphasizes a way forward for sustainable offshore operations. The study shows that the current state of knowledge is inexhaustive and will require further research to develop a design that minimizes interruption during remote harsh offshore operations. Resilient innovation, IoT and digitalization provide opportunities to fill some of the challenges of remote Arctic offshore operations.